The antioxidant system response to drought-stressed Diospyros lotus treated with exogenous melatonin - Peng Zhang; Yi Hu; Ruijin Zhou; Xiaona Zhang; Huiling Hu; Dongmei Lang (PeerJ, 2022)
Drought is one of the major abiotic stresses adversely impacting the growth of persimmon, which is a widely cultivated traditional fruit tree in North China. Melatonin is a bio-stimulator involved in mediating plant responses to drought. The role of exogenous melatonin application in the drought tolerance of Diospyros lotus was examined under drought stress with different doses of melatonin (0, 10, 50, and 100 µM). Exogenous melatonin application significantly mitigated the adverse effects of drought stress on chlorophyll fluorescence, lipid peroxidation, reactive oxygen species (ROS) accumulation and nitric oxide (NO) content. The 100-µM melatonin application produced the most beneficial impacts against drought stress. The melatonin-enhanced tolerance could be attributed to improved antioxidant enzymes, reduced drought-induced ROS accumulation, and lipid peroxidation. Melatonin application activated major antioxidant enzymes such as superoxide dismutase, catalase, peroxidase, glutathione reductase, and ascorbate peroxidase. Interestingly, NO concentration was significantly higher in 10 and 50 µM melatonin treatments and lower in 100 µM melatonin treatment compared to the control. Moreover, exogenous melatonin application affected the mRNA transcript levels of several genes involved in ROS metabolism, including DlRBOHA, DlSOD, DlCAT, and DlPOD. Hence, the responses of Diospyros lotus to drought varied with different doses of melatonin. Our results provide a concrete insight into the effects of melatonin with varying doses in alleviating drought as well as a platform for its potential application in the related fields.